Efeitos da enrofloxacina, da sulfaquinoxalina e da nicarbazina na dieta de galinhas de postura sobre a qualidade da casca do ovo - Raísa Gonçalves Dias (2019)
The eggshell quality of laying hens is defined by the degree of hygiene, integrity, strength and deformation. Some nutritional, management and environmental factors can cause loss of eggshell quality and among them are the use of some medications during the laying phase of the hens. With the aim of evaluating the quality of laying hens eggshell treated with antimicrobial sulfaquinoxaline and enrofloxacin and with coccidiostatic nicarbazin, 200 Lohmann brown laying hens (50 per treatment) with 60 weeks old were used. The treatments defined according to the antimicrobial or coccidiostatic provided to the hens via feed were as following: A) hens that received feed without medication from the first day to the 15th experimental day (control); B) hens that received sulfaquinoxaline at the concentration of 250 mg.kg-1 of feed from the first day to the 3rd day of the experiment; C) hens that received enrofloxacin at the concentration of 125 mg.kg -1 of feed from the first to the 5th day and; D) hens that received nicarbazin in the feed underdosage 40 mg.kg-1 of feed (with the intention of simulating the accidental contamination of the feed) from the first to the 5th day. After the treatment period, the hens of treatments B, C and D received feed without medication until the 15th experimental day. Eggs were collected from days 4th, 5th, 6th, 7th, 11th and 15th of the experimental period for the determinations of specific weight of the eggs and weight, percentage, resistance, thickness, porosity, coloration and calcium content of the eggshell. The observed results demonstrated a decrease in the percentages and increases in the porosities of the eggshells treated with sulfaquinoxaline, which resulted in a reduction in specific weight of the eggs. Eggs from chickens treated with enrofloxacin showed deformed eggshells and loss of color. The accidental use of nicarbazin in the laying hens feeding led to the depigmentation of eggshells. It was concluded that the treatment of hens with sulfaquinoxaline, enrofloxacin and nicarbazin during the laying period resulted in worsening of quality of the eggshells.